Study of Bamboos Through Establishment of Bambusetum in Arunachal Pradesh - Beniwal, B. S.; Haridasan, K. (Indian Forester, 1988)
The establishment of bambusetum at the Van Vigyan Kendra has triggered research on bamboos. Though a large number of bamboos were planted initially, many of them died due to wild animal damages and unfavourable climatic conditions for high altitude bamboos. The bambusetum could supply regularly rhizomes and planting stock to different aggencies. It will be worthwhile to create more such bambusetum covering different climatic zones. It is all the more essential for the high altitude bamboos. The bambusetum could also act as refuge for rare and endangered species of bamboos. Further observations could yield valuable results which could assist in better management and economy of bamboos.